A Clinicopathological Evaluation of the Patients with Supraclavicular Lymphadenopathy: A Retrospective Analysis - Mutlu, Fatih; Yaprak Bayrak, Büşra; Çakır, Özgür (ENT Updates, 2021)
Objective: The accuracy of biopsy technique and pathological reports from supraclavicular lymphadenopathy (ScLAP) biopsies in adults were evaluated. Methods: Five hundred sixty-four lymph node excisions or aspiration biopsies because of lymphadenopathy from all cervical regions were retrospectively assessed. Demographic and clinical data collected included gender, age, preoperative diagnosis, biopsy or cytology type, location of ScLAP, and biopsy diagnosis. Results: After exclusions for a variety of clinical and diagnostic reasons, the final analysis included 156 patients, of whom 34 (21.8%) underwent fine-needle aspiration (FNA), 69 (44.2%) core needle biopsy (CNB), and 53 (34%) excisional biopsies. In this study, 52 (33.3%) benign and 93 (59.6%) malignant diagnoses were reported. Totally, 11 of the 34 (32.3%) FNAs were insufficient for diagnosis. The size of the ScLAP (<10, 11-20, 21-30, >30 mm) did not affect malignancy risk. Patients aged > 55 years had a significantly greater likelihood of malignancy than younger patients. Logistic regression analysis showed that malignancy risk assessed by odds ratio (OR) was increased by male gender (P = .004; OR = 1.428; 95% CI 1.106-1.842), left side (P = .003; OR = 1.502; 95% CI 1.125-2.005) and age > 55 years (P = .007; OR = 2.631; 95%CI 1.275-5.431). Conclusion: Regardless of size, biopsy or cytology should be performed in all appropriate masses. Although the size of the lymph node had no effect on malignancy risk, male gender, older age, and left side were associated with a significant increase in the likelihood of malignancy.